Disinformation and counternarratives in international security : cognitive competition - Di??az Matey, Gustavo; Moral, Pablo (Routledge, 2026)
This book examines the strategic role of weaponized narratives and foreign information manipulation and interference (FIMI) in international relations.It aims to understand how information is used as a tool for power projection and strategic competition, combining theoretical and empirical analyses. The work covers both traditional disinformation and lesser-studied phenomena like information suppression and the psychosocial vulnerabilities that enable manipulation. Through case studies of information campaigns in both wartime and peacetime, it highlights the security challenges posed by these narratives across varying geopolitical tensions. The book bridges realist and constructivist approaches, considering the roles of state and non-state actors, as well as domestic populations and international organizations. With empirical studies of initiatives by NATO, the UN, and the EU, the volume equips readers to address critical questions about the success, influence, and impact of weaponized narratives and the effectiveness of efforts to counter them.This book will be of much interest to students of information warfare, foreign influence operations, foreign policy, and international relations.Chapter 1 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.
Keywords: Disinformation.; Security, International.; elektronické knihy; electronic books